2016
DOI: 10.1159/000451005
|View full text |Cite
|
Sign up to set email alerts
|

Is Extracorporeal Shock Wave Lithotripsy Really Safe in Long-Term Follow-Up? A Nationwide Retrospective 6-Year Age-Matched Non-Randomized Study

Abstract: Introduction: Shock wave lithotripsy (SWL) is widely used. However, several studies have reported increased blood pressure immediately after SWL. Until now, the association between SWL and new-onset hypertension has been a topic of discussion. This study is aimed at determining whether SWL leads to new-onset hypertension. Methods: Data were sourced from the Longitudinal Health Insurance Database 2000 of Taiwan, Republic of China, which was compiled from 1996 to 2010 using National Health Insurance data. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…5 In our study using our inclusion criteria, two new articles were included. 12,13 Both of these included studies showed a significant association between new-onset hypertension and patients with urolithiasis who underwent SWL. An update of the literature may be the cause of the inconsistency in the findings between the two meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 In our study using our inclusion criteria, two new articles were included. 12,13 Both of these included studies showed a significant association between new-onset hypertension and patients with urolithiasis who underwent SWL. An update of the literature may be the cause of the inconsistency in the findings between the two meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Tests for heterogeneity between the seven included studies were performed. [7][8][9][10][11][12][13] Heterogeneity was defined as P < 0.10 or I 2 > 50%. When homogeneity was adequate (P 0.10 or I 2 50%), a fixed-effects model was used for meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, additional surgical procedures are needed. Moreover, recurrence of kidney stones reaches over 50% after five years from the first stone, and 75% within 25 years (43). Recurrent renal colic is associated with the symptoms of both anxiety and depression (44).…”
Section: Side Effects Of Standard Treatments For Ksdmentioning
confidence: 99%